Laryngeal Metathesis in Saraiki Language - Firdos Atta; Nasir Abbas Syed; Saira Bano (Journal of Communication and Cultural Trends, 2023)
This study presents an analysis of synchronic metathesis in the Saraiki language based on the Optimality Theory (OT) approach. It is limited to the voiced laryngeal fricative (/ɦ/). Only voiced phonemes are the targets of /ɦ/ metathesis in Saraiki (resulting in breathy voiced consonants), while voiceless plosives are incompatible with this process. Metathesized and non-metathesized forms both occur in Saraiki. They are realized in informal and formal speech styles, respectively. This study analyses the informal speech style and identifies the reasons behind the movement of the above laryngeal fricative in phonetic optimization.